Dendritic Cell-Specific Intercellular Adhesion Molecule 3-Grabbing Nonintegrin/CD209 Is Abundant on Macrophages in the Normal Human Lymph Node and Is Not Required for Dendritic Cell Stimulation of the Mixed Leukocyte Reaction() - Granelli-Piperno, Angela (2005)
The C-type lectin dendritic cell-specific ICAM 3-grabbing nonintegrin (DC-SIGN)/CD209 efficiently binds several pathogens, including HIV-1. DC-SIGN is expressed on monocyte-derived DCs in culture, and importantly, it is able to sequester HIV-1 within cells and facilitate transmission of virus to CD4(+) T cells. To investigate DC-SIGN function, we have generated new mAbs. We report in this study that these and prior anti-DC-SIGN mAbs primarily label macrophages in the medullary sinuses of noninflamed human lymph node. In contrast, expression is not detected on most DCs in the T cell area, except for occasional cells. We also noted that IL-4 alone can induce expression of DC-SIGN in CD14(+) monocytes and circulating blood DCs. However, blockade of DC-SIGN with Abs and DC-SIGN small interfering RNA did not result in a major reduction in the capacity of these DCs to transfer HIV to T cells, confirming significant DC-SIGN-independent mechanisms. The blocking approaches did reduce HIV-1 transmission by DC-SIGN-transfected cells by >90%. DC-SIGN blockade also did not reduce the ability of DCs to stimulate T cell proliferation in the MLR. These results indicate that DC-SIGN has the potential to contribute to macrophage function in normal human lymph node, and that DCs do not require DC-SIGN to transmit HIV or to initiate T cell responses.